Co-targeting of metabolism using dietary and pharmacologic approaches reduces breast cancer metastatic burden - Qianying Zuo; Jin Young Yoo; Erik R. Nelson; Matthew J. Sikora; Rebecca B. Riggins; Zeynep Madak-Erdogan (npj Breast Cancer)
Abstract Patients with metastatic breast cancer face reduced quality of life and increased mortality rates, necessitating more effective anti-cancer strategies. Building on previous research that identified metastatic-niche-specific metabolic vulnerabilities, we investigated how a ketogenic diet enhances estrogen receptor (ER)-positive liver metastatic breast cancer’s response to Fulvestrant (Fulv) treatment. Using in vitro cell lines and in vivo xenograft metastasis mouse models, we examined the molecular mechanisms of combining ER targeting with a ketogenic diet. We found that Fulv treatment downregulates the ketogenesis pathway enzyme OXCT1, leading to β-hydroxybutyrate accumulation and decreased tumor cell viability. We also explored interactions between glucose, palmitic acid, and β-hydroxybutyric acid. These findings establish the molecular basis and clinical potential of a ketogenic diet to enhance Fulv efficacy in patients with ER+ liver metastatic breast cancer, potentially improving survival outcomes and quality of life in this population.